MUITAS ANTAS, POUCA GENTE? • ACTAS DO I COLÓQUIO INTERNACIONAL SOBRE MEGALITISMO - Rocha, Leonor (2010)
During survey work in January of 1996 in the area of Pavia, the author and Manuel Calado identified the alignment of Tera. At the time, five fallen menhirs were visible, forming a line oriented NW-SE. The following paper presents the results from the first archaeological intervention at the site.